Upaya meningkatkan kemampuan literasi matematika melalui media interaktif powerpoint di kelas x man 1 kota probolinggo: - - Al-furqany, Mirza Aulia (Maliki Interdisciplinary Journal, 2025)
Technological progress in the 21st century has profoundly influenced various sectors, especially education, including the integration of instructional methods. This research seeks to enhance the mathematical literacy of grade 10 students at MAN 1 Kota Probolinggo by utilizing interactive PowerPoint media integrated with the cooperative learning model, Student Teams Achievement Division (STAD). The study adopts a Classroom Action Research (CAR) design, carried out in two sequential cycles. Data were obtained through classroom observations and assessments of mathematical literacy grounded in contextual problem-solving tasks. A descriptive-comparative method was used to analyze the data across the different categories. A comparison between the first and second cycles revealed a substantial improvement in student performance, with the average score rising from 41.67 to 79.54—an increase of 37.88 points. According to Arikunto’s (2013) classification, in the second cycle, 16 out of 24 students (66.67%) achieved scores in the high category (76–100), 6 students (25%) were in the moderate category (56–75), and 2 students (8.33%) fell into the low category (≤55). These outcomes suggest that most students reached a high mastery level. As such, the integration of interactive PowerPoint media demonstrates a positive impact on improving the mathematical literacy of grade 10 students at MAN 1 Kota Probolinggo.